Investigating Language Perceptions in the Midwest with GIS - Benson, Erica J.; Khan, Anna; Williams, Anneli (My University, 2018)
The Midwest has a rich linguistic landscape but has been largely understudied within the realm of perceptual dialectology, which is what nonlinguistics think about the language in a particular region. This research aims to explore the perceptions of languages/dialects within the Midwest and determine if perceptions are affected by the type of state border on a map (solid or dashed line) and if they correlate with the sociocultural characteristics of people who perceive them. The use of map surveys, with solid or dashed outlines of the states, prompted research participants to draw and label dialect areas on a six-state map of the Midwest. The use of Geographic Information Systems (GIS) software and statistical analysis were utilized to find differences in responses to dashed-line and solid-line state borders on map surveys and correlations with demographic characteristics of research participants. Participants of varying backgrounds provided a diversity of demographics and spatial residency that were investigated for association of perceptions. This multidisciplinary research provides greater insight into linguistic perceptual dialectology in the Midwest, which may lead to materials to combat stereotypes and biases toward different ways of speaking.
Color poster with text, images, charts, and graphs.
Keywords: Linguistics; Geographic Information Systems; Posters